Opinion pooling - Elkin, Lee 1987-; Pettigrew, Richard (Cambridge elements. Elements in decision theory and philosophy, 2024)
Disagreement is a common feature of a social world. For various reasons, however, we sometimes need to resolve a disagreement into a single set of opinions. This can be achieved by pooling the opinions of individuals that make up the group. In this Element, we provide an opinionated survey on some ways of pooling opinions: linear pooling, multiplicative pooling (including geometric), and pooling through imprecise probabilities. While we give significant attention to the axiomatic approach in evaluating pooling strategies, we also evaluate them in terms of the epistemic and practical goals they might meet. In doing so, we connect opinion pooling to some philosophical problems in social epistemology and the philosophy of action, illuminating different perspectives one might take when figuring out how to pool opinions for a given purpose. This title is also available as Open Access on Cambridge Core.